Stylistique de l’hypotypose dans l’oeuvre romanesque de Marin Le Roy de Gomberville - Romagnino, Roberto (Acta Universitatis Lodziensis. Folia Litteraria Romanica, 2018)
This paper considers the treatement of hypotyposis in baroque French narrative fiction. After providing a definition of this figure, understood as a discourse particularly suited to the representation of a striking and pathetic « spectacle », the study focuses on its usage in the corpus of novels by Marin Le Roy de Gomberville, a successful author whose fictional production covers the 1619-1651 period. Through the stylistic study of some representative excerpts, this article aims to identify some elements of a rhetorics and a pragmatics of hypotyposis.